Ethnomathematical Exploration Batak Tribal Ulos Fabric design in the digital learning media of triangle and rectangular geometry - Purba, Martha Lestari; Hariyadi, Bambang; Zurweni, Zurweni; Haryanto, Haryanto (Universitas Trunojoyo Madura, 2025)
This study aims to explore the ethnomathematical values contained in the design of Ulos Batak fabric and its use in contextual digital learning media of mathematics on the topic of triangle and quadrilateral geometry. This type of research is qualitative descriptive (exploratory study) with a source triangulation method. The subjects of the study include Ulos craftsmen or distributors, mathematics teachers, and Batak tribal elders in Jambi City. Data collection was carried out through interviews, observations, documentation, and literature studies, then analyzed descriptively through data triangulation techniques to ensure the validity of the findings. The results of the study show that this ethnomathematics-based digital learning media has been validated by grade VIII mathematics teachers with an average percentage of 96.45% (very valid). This shows that motifs and patterns on Ulos cloth dominate contain geometric concepts, especially flat builds, which can be used as contextual learning media to support students' understanding of triangle and quadrilateral geometry material.Keywords: Ethnomathematics, Ulos Cloth, Digital Learning Media, Quadrilateral Triangle